2019
DOI: 10.1021/acs.chemmater.9b02887
|View full text |Cite
|
Sign up to set email alerts
|

Burying the Inverted Surface Dipole: Self-Assembled Monolayers Derived from Alkyl-Terminated Partially Fluorinated Alkanethiols

Abstract: The direction and magnitude of surface dipoles directly affect the interfacial properties and can be tuned through molecular design. This article examines the effect of a hydrocarbon−fluorocarbon, "HC−FC", dipole on the structural and interfacial properties of self-assembled monolayers (SAMs) as the dipole is buried into the film. A series of selectively fluorinated alkanethiols with a progressively extended alkyl chain atop six fluorocarbons and an alkyl spacer of 11 hydrocarbons, H(CH 2 ) n (CF 2 ) 6 (CH 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 66 publications
2
15
0
1
Order By: Relevance
“…Controlling and understanding the charge tunneling rate across a molecular framework and, in an ideal case, variation of this rate by external stimuli represent major challenges of molecular electronics. The great synthetic freedom allows us to vary both chemical composition of potential “device” molecules and their chemical and physical properties, such as, e.g., the proneness to reduction, oxidation, or protonation; possibility of quantum interference; and the availability of a certain dipole moment. The effect of the latter parameter on the charge transport properties of molecular systems represents a controversial issue, discussed in different contexts, such as its influence on the tunneling rate, molecule–electrode coupling, tuning of the transition voltage, dipole-induced rectification, etc. The standard way to vary the dipole moment for a molecule, assembled on an electrode and coupled to it via a suitable anchor, is its decoration with a dipolar tail group, even though the embedding of dipolar groups into the molecular backbone became increasingly popular recently. A simplest version of a dipolar tail group is represented by a single atom, such as a halogen one, possessing intrinsic electronegativity and polarizability. Indeed, the work function (WF) of both aliphatic and aromatic , self-assembled monolayers (SAMs) composed of such molecules can be varied via a single polarizable terminal atom, viz., F, Cl, Br, and I.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling and understanding the charge tunneling rate across a molecular framework and, in an ideal case, variation of this rate by external stimuli represent major challenges of molecular electronics. The great synthetic freedom allows us to vary both chemical composition of potential “device” molecules and their chemical and physical properties, such as, e.g., the proneness to reduction, oxidation, or protonation; possibility of quantum interference; and the availability of a certain dipole moment. The effect of the latter parameter on the charge transport properties of molecular systems represents a controversial issue, discussed in different contexts, such as its influence on the tunneling rate, molecule–electrode coupling, tuning of the transition voltage, dipole-induced rectification, etc. The standard way to vary the dipole moment for a molecule, assembled on an electrode and coupled to it via a suitable anchor, is its decoration with a dipolar tail group, even though the embedding of dipolar groups into the molecular backbone became increasingly popular recently. A simplest version of a dipolar tail group is represented by a single atom, such as a halogen one, possessing intrinsic electronegativity and polarizability. Indeed, the work function (WF) of both aliphatic and aromatic , self-assembled monolayers (SAMs) composed of such molecules can be varied via a single polarizable terminal atom, viz., F, Cl, Br, and I.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, increasing the length of the hydrocarbon chain atop the terminal dipole, effectively burying the dipole into the film, caused the contact angle value to start anew, with the fluorocarbons serving as a surrogate substrate. 8 These findings provided unequivocal evidence for the influence of surface dipoles on the macroscopic wettability of surfaces. 4,5,7,8 Despite the many studies analyzing the structure of fluorinated SAMs in comparison to their contact angle wettability, 9,10 there remains insufficient information regarding the liquid structure at the SAM interface, perhaps due to the limited number of techniques with the capacity to survey buried interfaces.…”
Section: ■ Introductionmentioning
confidence: 80%
“…Self-assembled monolayers (SAMs) derived from the adsorption of alkanethiols on gold provide conformationally ordered organic thin films with a precise orientation of the terminal functional groups. Studies undertaken to determine SAM structure and organization when in contact with liquids have shown the composition and orientation of the terminal group strongly influences the wettability of the SAMs. Recently, Zenasni et al, using selectively fluorinated SAMs on gold with oppositely oriented dipoles at the chain termini, concluded that an inversion of the terminal dipole in a monolayer film can cause a reversal of the odd–even wettability effect with polar contacting liquids . Furthermore, increasing the length of the hydrocarbon chain atop the terminal dipole, effectively burying the dipole into the film, caused the contact angle value to start anew, with the fluorocarbons serving as a surrogate substrate . These findings provided unequivocal evidence for the influence of surface dipoles on the macroscopic wettability of surfaces. ,,, Despite the many studies analyzing the structure of fluorinated SAMs in comparison to their contact angle wettability, , there remains insufficient information regarding the liquid structure at the SAM interface, perhaps due to the limited number of techniques with the capacity to survey buried interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we primarily focus on work performed recently in the groups of the authors. It should, however, also be mentioned that in the literature there are several other examples of embedded-dipole SAMs. Moreover, in the discussion we largely concentrate on thiolate SAMs on gold in view of the broad use of these systems both in basic research and in applications …”
Section: Introductionmentioning
confidence: 99%